Biochemical features of a Protoceratium reticulatum red tide in Chipana Bay (Northern Chile) in summer conditions - Rossi, Sergio; Fiorillo, Ida (Scientia Marina, 2010)
Protoceratium reticulatum is considered a potential toxic dinoflagellate. This paper describes a high-frequency monitoring study performed at Chipana Bay (northern Chile), sampling over 48 hours in a near-bottom shallow coastal area to quantify the biochemical features of a red tide dominated by this microscopic algae. This area belongs to the Humboldt Current upwelling system, and is considered highly productive for artisanal fisheries. Total chlorophyll a, total lipids, particulate organic carbon and nitrogen, fatty acids and major phytoplankton group concentration (i.e. dinoflagellates, diatoms, ciliates and cysts) were studied in 7-hour intervals in February 2007. Our results indicate a high concentration of potential available food in the form of lipids ranging from 50 to 300 μg L-1 for benthic suspension feeders, i.e. bivalves. The dominance of P. reticulatum (60-80% of the total cell concentration per litre, ranging from 55x103 to 384x103 cells L-1) can be considered as a possible interference for harvesting in this productive area, although the toxicity of this algae was not proved in the present study. The main dinoflagellate fatty acid markers [18:0, 18:4(n-3), 20:5(n-3), and 22:6(n-3)] showed high proportions (%) during the short time cycle and in at least two cases [the 18:4 (n-3) and 22:6 (n-3) fatty acids] a highly significant relationship with dinoflagellate concentration (cells L-1). The topographical and benthic structure (mainly kelp forest) of the zone helps to retain particles and nutrients that may in part explain the high productivity and food availability, but the presence of recurrent red tides in this coastal area—if they prove to be toxic—is argued to be a major problem for local fisheries.